Aucubin Alleviates Intervertebral Disc Degeneration by Repressing NF-κB-NLRP3 Inflammasome Activation in Endplate Chondrocytes - Zou K; Ying J; Xu H; Zeng Q; Huang H; Chen W; Li X; Wang P; Jin H; Li J; Wu Y (Dove Medical Press, 2023)
Kaiao Zou,1,2,* Jun Ying,3,* Huihui Xu,1,2 Qinghe Zeng,1,2 Haipeng Huang,1,2 Wenzhe Chen,1,2 Xuefeng Li,1,2 Pinger Wang,1 Hongting Jin,1 Ju Li,3 Yungang Wu4 1Institute of Orthopaedics and Traumatology of Zhejiang Province, The First Affiliated Hospital of Zhejiang Chinese Medical University (Zhejiang Provincial Hospital of Chinese Medicine), Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310006, People's Republic of China; 2The First College of Clinical Medicine, Zhejiang Chinese Medical University, Hangzhou, People's Republic of China; 3Department of Orthopaedics, The First Affiliated Hospital of Zhejiang Chinese Medical University (Zhejiang Provincial Hospital of Chinese Medicine), Hangzhou, People's Republic of China; 4Department of the Orthopedics of TCM, First Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang Province, 325000, People's Republic of China*These authors have contributed equally to this workCorrespondence: Yungang Wu; Ju Li, Email zjwyg@126.com; juli@zcmu.edu.cnBackground: Intervertebral disc degeneration (IDD) is a prevalent degenerative disease and often recognized as the primary cause of lower back pain (LBP). Aucubin (Au) is a natural compound with anti-inflammatory properties in various diseases. The present study aimed to confirm the therapeutic effect of Au on IDD and explore its potential mechanism in vivo and in vitro.Methods: The process of IDD was simulated using the lumbar spine instability (LSI) model. In vivo, the therapeutic effect of Au on LSI-induced mice was evaluated by micro-CT and histomorphometry. Additionally, immunohistochemistry was applied to detect the cartilage metabolism and inflammasome activation in endplate. In vitro, the cytotoxicity of Au on ATDC5 cells was detected by Cell Counting Kit-8 (CCK-8), and the biological effects of Au were evaluated by Quantitative Real-time PCR (qRT-PCR) and Western blotting.Results: Micro-CT analysis showed that Au administration significantly alleviated LSI-induced disc volume narrowing and endplate cartilage degeneration, which was further supported by Alcian Blue Hematoxylin/Orange G (ABH/OG) staining. Immunohistochemistry results verified that Au could increase the expression of Col2α 1 and Aggrecan, reduce the expression of Mmp-13, and attenuate the degradation of the endplate extracellular matrix (ECM). Mechanistically, we found that Au treatment, both in vivo and in vitro, significantly inhibited NF-κB-NLRP3 inflammasome activation in chondrocytes as determined by the decreased expression of p-P65, NLRP3, and Caspase-1.Discussion: Taken together, our findings have demonstrated for the first time that Au treatment ameliorated the degeneration of cartilage endplates in IDD may by inhibiting NF-κB-NLRP3 inflammasome activation in chondrocytes and provided a potential candidate for the treatment of IDD.Keywords: Aucubin, cartilage endplate, intervertebral disc degeneration, NF-κB-NLRP3, inflammasome